2018
DOI: 10.3390/app8091639
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Contact Pressure and Thermo-Elastic Behavior of a Brake Disc-Pad by Infrared Images and Finite Element Analysis

Abstract: Featured Application: Design and performance evaluation of disc/pad; drum/shoe; friction clutches, etc.Abstract: To understand the tribological characteristics of a frictional brake system, it is very important to measure the contact pressure between the brake disc and pads. But until now there have been no direct methods by which to measure the contact pressure. In this study, an attempt to indirectly estimate the contact pressure is proposed. Infrared thermal images and finite element analysis were used as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…The relation in Equation 14confers that the braking torque depends on the radial dimensions of the friction surface without being influenced by angular dimensions. But a larger surface area has an advantage of better heat dissipation [6].…”
Section: Braking Torquementioning
confidence: 99%
See 1 more Smart Citation
“…The relation in Equation 14confers that the braking torque depends on the radial dimensions of the friction surface without being influenced by angular dimensions. But a larger surface area has an advantage of better heat dissipation [6].…”
Section: Braking Torquementioning
confidence: 99%
“…Transparency and stability are the main requirements in the design of a haptic device that guarantee its high-fidelity feedback display to correctly simulate the physical environment [4]. Haptic interfaces mainly consist of active [5] and/or passive [6] actuators; those have the tendency to provide counter sensations as a result of human interaction. The key considerations in designing these actuators for haptic applications are the output forces/torques/vibrations, response time, power consumption, volume, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bode et al [33] proposed a numerical model able to consider the heterogeneity of the friction material and, therefore, sensible to changes in the material composition. Furthermore, Goo [34] concluded that an infrared camera combined with FEA could be used to study the contact pressure and thermo-elastic behaviour. No studies known to the authors combined a macroscopic thermal simulation approach with a meso-scale approach to evaluate the influence of the copper in the friction material on the local contact temperature under the real macro-level boundary conditions.…”
Section: Of 23mentioning
confidence: 99%
“…2 The friction-heat-vibration coupling phenomenon and the resulting issues have become key points of the disc brake study. In the temperature and thermal stress field, Goo 3 measured the contact pressure of the brake disc-pad to understand the tribological characteristics of a frictional brake system. Wang et al 4 investigated the temperature evolution of the railway vehicle brake disc during high-speed braking by using in situ experiments, theoretical analysis, and finite element modeling.…”
Section: Introductionmentioning
confidence: 99%